The Influence of Profitability, Liquidity and Leverage on Firm Value in Palm Oil Plantation Companies Listed on the Indonesian Stock Exchange (BEI) for the 2019-2021 Period - Ramadhan, Rizki; Aulia, Muhammad Faqih; Rismadi; Fauziah, Sri Rani; Arfiani, Mutia; Hilmi (Jurnal Akuntansi Terapan dan Bisnis, 2024)
The aim of this research is to see how profitability, liquidity and leverage impact the value of palm oil companies listed on the Indonesia Stock Exchange during the 2019-2021 period. This research covers all palm oil companies listed on the Indonesia Stock Exchange (BEI). Sampling was carried out purposively based on specific criteria, which resulted in 36 data samples for research. The data used is secondary data taken from financial reports. Multiple linear regression analysis was used to analyze the data. The research results show that while liquidity and profitability do not affect firm value in oil palm plantations for the 2019-2021 period, leverage does affect firm value.